Identifying Facilitators and Barriers of Electronic Medical Record (EMR) Implementation in Hospitals: a Scoping Review - Fitria - Hayati; Ahsan Ahsan; Fransiska Imavike Fevriasanty (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Electronic Medical Records (EMR) as a form of healthcare digitalization, aim to improve the effectiveness, efficiency, and quality of healthcare. However, the transition from paper-based systems remains limited in many countries and continues implementation challenges. review aims to identify facilitators and barriers of EMR implementation among healthcare workers in hospitals settings. The study design used was a scoping review. A comprehensive search was conducted using the PCC (Population-Concepts-Context) strategy, using terms related to factors influencing the implementation of EMR by healthcare workers in hospitals, in four databases (ProQuest, ScienceDirect, PubMed, and Google Scholar) for studies from 2020 - 2025. Article selection was performed using the PRISMA-ScR guidelines. A total of twenty-eight studies met the inclusion criteria. The findings indicate that facilitators and barriers of EMR implementation emerge from the interaction between staff-related, organization, and technological factors. Key facilitators include digital literacy, organizational training support, and system quality. Major barriers involve low staff readiness, insufficient organizational support, and technology quality and complexity issues. Most studies conducted in low- and middle-income countries (LMICs) reported staff-related factors as facilitators and barriers of EMR implementation. Thus, effective implementation strategies need to be designed contextually through the simultaneous strengthening of human resource capacity, organizational support, and technological quality.